Crafting a Republic for the World : Scientific, Geographic, and Historiographic Inventions of Colombia - Del Castillo, Lina (Book collections on Project MUSE., 2018)
"An examination of how the development of geography practices, disciplines, and technologies intertwined with the process of modern nation-state formation in Colombia from 1821 to 1921"--Provided by publisher.